Dry‐stone wall terrace monitoring and modelling. (17th April 2018) - Preti, Federico; Errico, Alessandro; Caruso, Marco; Dani, Andrea; Guastini, Enrico
Abstract: Dry‐stone wall agricultural terraces are widespread all over the world and represent an effective retaining structure for farming purposes. However, dry‐stone walls can be subjected to degradation and damages, with complex and expensive maintenance. Such high costs are the most relevant drivers of land abandonment in many agricultural areas of Europe and of other continents, resulting in a progressive loss of cultivable surface, cultural heritages, and landscape traditional elements. Therefore, a more effective and efficient management of these systems is needed. As a contribution, in the present paper, an innovative modelling approach system is proposed. The presented model is able to describe hydrological processes on a terraced slope and to analyze the destabilizing pressures acting on the retaining dry‐stone walls in the most critical portion of each terrace. The model structure is based on the results of multidisciplinary field monitoring campaigns on water circulation in terraced landscapes carried out on a terraced vineyard (Lamole, Tuscany, Italy). A monitoring station was set up on a recently reconstructed dry‐stone wall, to measure the parameters influencing the pressures acting on the retaining structure. The results show a good capability of the model to predict the distribution and intensity of stresses on the instrumented dry‐stone wall over time and space. Such stresses were related to the earth pressure and to hydrostatic pressures (water accumulation), without the occurrence of soil saturation. Detecting the most failure‐prone portions of a terraced system, this approach can support landowners and land planners in managing these complex and fragile environments.